A COMPARATIVE BIO-KINEMATIC ANALYSIS OF LUNGE INITIATION BEFORE AND AFTER FRONT FOOT CONTACT IN FOIL FENCING - Essa, Ali Abdallah; Gary, Sameer Khalaf; Daikh, Yarob Abdul Baqi (Journal Olahraga Rekat (Rekreasi Masyarakat), 2026)
Background. Biomechanics played a major role in these contributions, as it details and explains the function of each part of the body and studies each technique, its effectiveness, and what a particular technique can achieve in fulfilling the purpose of the movement. Objectives. This study aimed to identify differences in selected bio-kinematic variables between initiating a lunge prior to versus following front foot ground contact in foil fencing. Method. The researchers used the descriptive method with a comparative analytical approach as the optimal method for solving the research problem. The descriptive method is defined as the accurate description of a phenomenon or problem and studying the phenomenon as it is in reality, The research community was identified as four players of the Iraqi national foil team. In order to obtain a result that is close to reality, the research sample consisted of 24 attempts made by the players for both cases. The sample was chosen purposively, as only the two cases of stabbing were studied, and for more than one match, as the total number of matches reached (3) National team players are chosen because they have a high level of physical and technical capabilities due to the need to study for this level. The research sample consisted of four fencers from the Iraqi National Foil Team. Results. There is a significant difference between the thrust before and after the anchorage in the variable of knee joint angle, as the value of T was equal to (-5.383). The significant difference between the lunge before and after landing in the shoulder joint angle variable, where the T value was (-3.590). T value for the dueling distance variable was (2.509), as the T value was (3.444). And there is a significant difference in the step distance variable and in favor of stabbing after fulcrum, as the value of T was (-2.933). Conclusion. The study reached several conclusions; primarily, the results revealed significant differences in certain bio kinematic variables between the pre-contact and post-contact lunge techniques, while other variables showed no significant differences between the two styles. Based on the findings, the researchers recommended that coaches train athletes in both lunge techniques due to their significant impact on match outcomes.